Kashi Ageti enriches vegetable basket - Sanwal, S K; Kumar, Rajesh (Indian Horticulture, 2019)
Kashi Ageti is a new pea variety of early maturity group. It is ideal for zone IV (Uttar Pradesh, Bihar, Jharkhand and Punjab) of the country. It is high-yielding and more sweet than the popularly grown variety, Arkel.